Skala Kesantunan Tuturan dalam Acara 1 Jam 1OOO Pesan di Yotube VDVC Talk - Dwi Aprilla Wahyuni; Alber Alber (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research is based on someone who easily gives opinions or speaks without paying attention to language politeness. This study discusses the scale of speech politeness in the 1 Hour 1000 Message program on youtube VDVC talk. The purpose of this study was to obtain information, describe, and analyze, the speech politeness scale in the 1 Hour 1000 Message program on youtube VDVC Talk. The theory that is used as the basis is Leech, Chaer (2010). The method used is the method of content analysis (content analysis). The approach used is a qualitative approach. The data source of this research is video in the event 1 Hour 1000 Messages on youtube VDVC Talk. The data collection technique uses documentation techniques, free listening and conversation techniques, and note-taking techniques. The data analysis technique used is content analysis or content analysis proposed by Bungin. The results of the study of 98 speech data after being analyzed became 129 speech data. From 129 speech data, 91 speeches are polite and 38 are not polite. Based on the data obtained, the 1 Hour 1000 Messages event on YouTube VDVC Talk, belongs to the polite category. politeness when speaking can occur because it is influenced by several factors, one of which is a lack of respect for each other.